Twenty-four-hour blood pressure and CSF biomarkers of Alzheimer’s disease and related dementias in a community cohort - Madeline Gibson; William T. O’Brien; Ella Rowsthorn; Katherine H. Franks; Lachlan Cribb; Marina Cavuoto; Beaudan Campbell-Brown; Ian Harding; Meng Law; Trevor T.-J. Chong; Stuart J. McDonald; Terence J. O’Brien; et al. (GeroScience, 2026)
Hypertension in midlife is associated with increased dementia risk, yet its relationship with early pathological changes of Alzheimer’s disease and related dementias (ADRD) remains unclear. Unlike office blood pressure (BP), 24-h ambulatory BP (ABPM) may better reflect cardiovascular risk, but associations between 24-h BP measures with ADRD biomarkers are unknown. This cross-sectional study examined associations between BP and cerebrospinal fluid biomarkers of ADRD in mid-to-late life. Dementia-free participants ( n = 77; mean age = 67 [SD, 6]; 39% women) from the community-based Brain and Cognitive Health (BACH) cohort underwent office and 24-h ABPM assessments to calculate mean BP, nocturnal dipping, blood pressure variability (BPV, coefficient of variation) across 24-h, awake and asleep periods. Participants also completed a lumbar puncture to assess ADRD biomarkers: Aβ42/Aβ40 ratio, phosphorylated tau at threonine 217 (pTau217), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL). Linear regression models examined associations between BP and ADRD biomarkers, adjusting for age, sex, BMI, smoking, anti-hypertensive medication use, and APOE ε4 status. Higher 24-h and awake mean BP were associated with higher GFAP (24-h: per 1-SD unit increase, β = 1606.6 pg/mL, p = .03; awake: β = 1668.pg/mL, p = .03) and NfL (24-h: β = 172.3 pg/mL, p = .03; awake: β = 162.3 pg/mL, p = .04) levels. Elevated asleep BPV was associated with higher Aβ42/Aβ40 ratio ( β = 0.01, p = .01). No, other clear associations were identified for the other BP metrics ( p > .05 for all). Findings indicate that elevated BP is associated with neuronal injury and astrocytic reactivity, suggesting possible pathways through which BP may relate to neurodegenerative processes, independent of overt amyloid or tau.

A qualitative exploration of women's experiences of food insecurity around pregnancy aligned with the socio-ecological model - J. Marshall; L. Davies; Lambeth HDRC; F. Lavelle; N. O'Leary; A.C. Flynn; S. Harding; Z. Bell (Appetite, 2026)

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Molecular epidemiology and evolution of norovirus in Australia and New Zealand, 2018 to 2020 - Grace J. H. Yan; Joanne Hewitt; Lewis K. Mercer; Emma F. Harding; Dawn Croucher; Alice G. Russo; Peter G. Huntington; Jason M. Mackenzie; William D. Rawlinson; Peter A. White (Infectious Diseases, 2025)

Developing high-concentration monoclonal antibody formulations for subcutaneous administration to improve patient treatment - Laura R. R. Mijangos; Stephen E. Harding; Nicholas J. Darton (Biophysical Reviews, 2025)
The transition of immunotherapy administration from intravenous infusion to subcutaneous (SC) administration of monoclonal antibody formulations for oncology patients has garnered significant interest. SC administration offers multiple benefits, including potential for at-home administration, enhanced patient compliance, reduced hospital congestion, lowered health care costs, and improved sustainability by reducing drug wastage and minimizing environmental impact. However, for many biologics, the shift to SC administration requires the development of high-concentration monoclonal antibody products (HCmAP) due to the need for large dose volumes. Here we explore the impact of the COVID-19 pandemic on immunotherapy administration and the imperative of adopting SC administration. We discuss challenges encountered throughout the manufacturing, shipping, storage, and delivery of HCmAP. A central hurdle identified involves the biophysical instability and the large increase in viscosity of these biologics due to increased antibody concentration. Further complications can arise from “non-ideality” effects through molecular crowding or co-exclusion effects (macromolecules blocking the free movement in solution of other macromolecules) and elevated macromolecular interactions. For reducing the viscosity for a given concentration of antibody, the main excipients reported are salts and amino acids, with Arg-HCl demonstrating particularly improved formulation viscosity in an HCmAP. However, excipients with viscosity-lowering effects can also impact protein stability. The journey to discover suitable excipient strategies remains ongoing, combined with emerging approaches such as molecular engineering and computational techniques, with the ultimate aim of facilitating the successful integration of SC administration for economic savings, environmental sustainability, and social equity.

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

GLOSSAQUA : A global dataset of size spectra across aquatic ecosystems - Zeynep Ersoy; Charlotte Evangelista; Aitor Larrañaga; Daniel M. Perkins; Javier Sánchez‐Hernández; Teofana Chonova; David Cunillera‐Montcusí; Carmen García‐Comas; Jorge García‐Girón; Ioar de Guzman; Justin Pomeranz; Victor Saito; et al. (Ecology, 2025)
Body size is a key trait in ecology due to its influence on metabolism and many other life‐history traits that affect population and community responses to environmental variation as well as ecosystem properties. The size spectrum represents the relationship between abundance (or biomass) and body size, independent of species identity. Size spectrum parameters, such as the slope or intercept, have been applied extensively as indicators of ecological status across multiple ecosystem types. The GLOSSAQUA dataset includes data from mainly heterotrophic communities composed of single (e.g., zooplankton, macroinvertebrates, or fish) to multiple taxonomic groups (e.g., from primary consumers to apex predators, and phytoplankton to large zooplankton), across diverse spatial and temporal scales, from surveys in freshwater (43% studies), marine (52% studies) and brackish (5% studies) ecosystems. In total, we compiled a unique global dataset of 8459 size spectrum slopes or exponents, 5237 intercepts, and 4,497 linearity coefficients (i.e., defined by the R 2 of the linear fit of the size spectrum) from 127 articles and gray literature (i.e., unpublished datasets). The current dataset aims to help identify the main drivers shaping aquatic size spectrum parameters at a global scale and contribute to cross‐ecosystem comparisons. GLOSSAQUA can serve to explore questions such as factors influencing spatial and temporal dynamics of community size structure, comparing the response of community size structure between natural versus human‐impacted sites, and comparing global patterns in different aquatic ecosystems. We encourage researchers, especially those from underrepresented geographical areas (e.g., South Hemisphere and Asia) to fuel this dataset in the future. The dataset is provided under a CC‐BY‐NC‐S4 4.0 license, and users are encouraged to cite this data paper when using the data.

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Temporal and Spatial Dynamics of Synechococcus Clade II and Other Microbes in the Eutrophic Subtropical San Diego Bay - Katie J. Harding; Maitreyi Nagarkar; Maggie Wang; Kailey Ramsing; Niv Anidjar; Sarah Giddings; Bianca Brahamsha; Brian Palenik (Environmental Microbiology, 2025)
The diversity of the marine cyanobacterium Synechococcus can be broadly separated into clades, with clade II typically present in warm oligotrophic water, and clades I and IV found in cooler coastal water. We found amplicon sequence variants (ASVs) belonging to clade II in the nutrient‐replete waters of San Diego Bay (SDB). Using the 16S rRNA gene, 18S rRNA gene and internal transcribed spacer region sequencing, we analysed multiple locations in SDB monthly for over a year, with additional samples dating back to 2015. Synechococcus community composition differed from the nearby coast into SDB in terms of dominant clade and ASVs. Specific clade II ASVs became relatively more abundant towards the back of the bay and showed seasonality, with higher relative abundance in the warm months. Select ASVs group phylogenetically and show similar seasonal and spatial distribution patterns, indicating these ASVs have adapted to SDB. Isolates matching clade II ASVs from SDB show pigment composition that is better adapted to the green light available in SDB, further supporting our findings. Other microbial taxa also show SDB enrichment, providing evidence that SDB is a chemostat‐like environment where circulation, temperature, light and other environmental conditions create a zone for microbial evolution and diversification.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

P05-12 New methods for the early characterisation of drug-induced liver toxicity - G. Bocci; C. Archer; J. Harding; D.E.V. Pires (Toxicology Letters, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

LP-18: Challenges and Opportunities in Use of the Minipig for Nonclinical Pharmaceutical Development: Results of the Second IQ DruSafe Minipig Survey - J. Harding; K. Datta; D. Olaharski; D. Clarke; T. Flandre; K. French; M. Leach; S. Mohr; D. Strein; B. Gauthier (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

Schomburginones A‒J, geranylated benzophenones from the leaves of Garcinia schomburgkiana and their cytotoxic and anti-inflammatory activities - Edwin R. Sukandar; Sutin Kaennakam; Sutthida Wongsuwan; Jaruwan Chatwichien; Sucheewin Krobthong; Yodying Yingchutrakul; Thanisorn Mahatnirunkul; Fadjar Mulya; Vudhichai Parasuk; David J. Harding; Preeyaporn Poldorn; Thanyada Rungrotmongkol; et al. (Phytochemistry, 2023)

Experimental support for reclassification of the light scattering second virial coefficient from macromolecular solutions as a hydrodynamic parameter - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (European Biophysics Journal, 2023)
This investigation examines the source of the disparity between experimental values of the light scattering second virial coefficient $${A}_{2}$$ A 2 (mL.mol/g 2 ) for proteins and those predicted on the statistical mechanical basis of excluded volume. A much better theoretical description of published results for lysozyme is obtained by considering the experimental parameters to monitor the difference between the thermodynamic excluded volume term and its hydrodynamic counterpart. This involves a combination of parameters quantifying concentration dependence of the translational diffusion coefficient obtained from dynamic light scattering measurements. That finding is shown to account for observations of a strong correlation between $${A}_{2}{M}_{2}$$ A 2 M 2 (mL/g), where M 2 is the molar mass (molecular weight) of the macromolecule and the diffusion concentration parameter $${k}_{D}$$ k D (mL/g). On the grounds that $${k}_{D}$$ k D is regarded as a hydrodynamic parameter, the same status should be accorded the light scattering second virial coefficient rather than its current incorrect thermodynamic designation as $${B}_{2}$$ B 2 (mL.mol/g 2 ), or just B , the osmotic second virial coefficient for protein self-interaction.

Retrospective rationalization of disparities between the concentration dependence of diffusion coefficients obtained by boundary spreading and dynamic light scattering - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (European Biophysics Journal, 2023)
This study establishes the existence of substantial agreement between published results from traditional boundary spreading measurements (including synthetic boundary measurements in the analytical ultracenrifuge) on two globular proteins (bovine serum albumin, ovalbumin) and the concentration dependence of diffusion coefficient predicted for experiments conducted under the operative thermodynamic constraints of constant temperature and solvent chemical potential. Although slight negative concentration dependence of the translational diffusion coefficient is the experimentally observed as well as theoretically predicted, the extent of the concentration dependence is within the limits of experimental uncertainty inherent in diffusion coefficient measurement. Attention is then directed toward the ionic strength dependence of the concentration dependence coefficient ( $${k}_{D}$$ k D ) describing diffusion coefficients obtained by dynamic light scattering, where, in principle, the operative thermodynamic constraints of constant temperature and pressure preclude consideration of results in terms of single-solute theory. Nevertheless, good agreement between predicted and published experimental ionic strength dependencies of $${k}_{D}$$ k D for lysozyme and an immunoglobulin is observed by a minor adaptation of the theoretical treatment to accommodate the fact that thermodynamic activity is monitored on the molal concentration scale because of the constraint of constant pressure that pertains in dynamic light scattering experiments.

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

Chemical and Water-Isotope Composition Unravels the Source and Evolution of the Kittilä Underground Mine Water, Kiistala, Finland - V. Milesi; J. Declercq; W. Harding; T. Jarman; O. Baas; J. Saukkoriipi; A. van Wageningen; R. Bowell (Mine Water and the Environment, 2023)

Wind regime changes in the Euro-Atlantic region driven by Late-Holocene Grand Solar Minima - P. Harding; C. Martin-Puertas; J. Sjolte; A. A. Walsh; R. Tjallingii; C. Langdon; S. P. E. Blockley; A. Brauer; P. Langdon; A. M. Milner; R. Muscheler; M. Perez (Climate Dynamics, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Highly contaminated river otters (Lontra canadensis) are effective biomonitors of environmental pollutant exposure - Michelle Wainstein; Louisa B. Harding; Sandra M. O’Neill; Daryle T. Boyd; Fred Koontz; Bobbi Miller; Cornelya F. C. Klütsch; Philippe J. Thomas; Gina M. Ylitalo (Environmental Monitoring and Assessment, 2022)
River otters ( Lontra canadensis ) are apex predators that bioaccumulate contaminants via their diet, potentially serving as biomonitors of watershed health. They reside throughout the Green-Duwamish River, WA (USA), a watershed encompassing an extreme urbanization gradient, including a US Superfund site slated for a 17-year remediation. The objectives of this study were to document baseline contaminant levels in river otters, assess otters’ utility as top trophic-level biomonitors of contaminant exposure, and evaluate the potential for health impacts on this species. We measured a suite of contaminants of concern, lipid content, nitrogen stable isotopes (δ 15 N), and microsatellite DNA markers in 69 otter scat samples collected from twelve sites. Landcover characteristics were used to group sampling sites into industrial (Superfund site), suburban, and rural development zones. Concentrations of polychlorinated biphenyls (PCBs), polybrominated diphenyl ether flame-retardants (PBDEs), dichlorodiphenyl-trichloroethane and its metabolites (DDTs), and polycyclic aromatic hydrocarbons (PAHs) increased significantly with increasing urbanization, and were best predicted by models that included development zone, suggesting that river otters are effective biomonitors, as defined in this study. Diet also played an important role, with lipid content, δ 15 N or both included in all best models. We recommend river otter scat be included in evaluating restoration efforts in this Superfund site, and as a potentially useful monitoring tool wherever otters are found. We also report ΣPCB and ΣPAH exposures among the highest published for wild river otters, with almost 70% of samples in the Superfund site exceeding established levels of concern.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Cover Image - Lewis K. Mercer; Emma F. Harding; Grace J. H. Yan; Peter A. White (Journal of Fish Diseases, 2022)

Novel viruses discovered in the transcriptomes of agnathan fish - Lewis K. Mercer; Emma F. Harding; Grace J. H. Yan; Peter A. White (Journal of Fish Diseases, 2022)

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

Secondary metabolites from cultures of the ant pathogenic fungus Ophiocordyceps irangiensis BCC 2728 - Siriporn Saepua; Jittra Kornsakulkarn; Patchanee Auncharoen; Pranee Rachtawee; Surisa Kongthong; Nattawut Boonyuen; David J. Harding; Tatsuo Nehira; Tienthong Thongpanchang; Chawanee Thongpanchang (Natural Product Research, 2021)

The genetic architecture of target‐site resistance to pyrethroid insecticides in the African malaria vectors Anopheles gambiae and Anopheles coluzzii - Chris S. Clarkson; Alistair Miles; Nicholas J. Harding; Andrias O. O’Reilly; David Weetman; Dominic Kwiatkowski; Martin J. Donnelly (Molecular Ecology, 2021)
Resistance to pyrethroid insecticides is a major concern for malaria vector control. Pyrethroids target the voltage‐gated sodium channel (VGSC), an essential component of the mosquito nervous system. Substitutions in the amino acid sequence can induce a resistance phenotype. We use whole‐genome sequence data from phase 2 of the Anopheles gambiae 1000 Genomes Project (Ag1000G) to provide a comprehensive account of genetic variation in the Vgsc gene across 13 African countries. In addition to known resistance alleles, we describe 20 other non‐synonymous nucleotide substitutions at appreciable population frequency and map these variants onto a protein model to investigate the likelihood of pyrethroid resistance phenotypes. Thirteen of these novel alleles were found to occur almost exclusively on haplotypes carrying the known L995F kdr (knock‐down resistance) allele and may enhance or compensate for the L995F resistance genotype. A novel mutation I1527T, adjacent to a predicted pyrethroid‐binding site, was found in tight linkage with V402L substitutions, similar to allele combinations associated with resistance in other insect species. We also analysed genetic backgrounds carrying resistance alleles, to determine which alleles have experienced recent positive selection, and describe ten distinct haplotype groups carrying known kdr alleles. Five of these groups are observed in more than one country, in one case separated by over 3000 km, providing new information about the potential for the geographical spread of resistance. Our results demonstrate that the molecular basis of target‐site pyrethroid resistance in malaria vectors is more complex than previously appreciated, and provide a foundation for the development of new genetic tools for insecticide resistance management.

ASL expression in ALDH1A1+ neurons in the substantia nigra metabolically contributes to neurodegenerative phenotype - Shaul Lerner; Raya Eilam; Lital Adler; Julien Baruteau; Topaz Kreiser; Michael Tsoory; Alexander Brandis; Tevie Mehlman; Mina Ryten; Juan A. Botia; Sonia Garcia Ruiz; Alejandro Cisterna Garcia; et al. (Human Genetics, 2021)
Argininosuccinate lyase (ASL) is essential for the NO-dependent regulation of tyrosine hydroxylase (TH) and thus for catecholamine production. Using a conditional mouse model with loss of ASL in catecholamine neurons, we demonstrate that ASL is expressed in dopaminergic neurons in the substantia nigra pars compacta, including the ALDH1A1 + subpopulation that is pivotal for the pathogenesis of Parkinson disease (PD). Neuronal loss of ASL results in catecholamine deficiency, in accumulation and formation of tyrosine aggregates, in elevation of α-synuclein, and phenotypically in motor and cognitive deficits. NO supplementation rescues the formation of aggregates as well as the motor deficiencies. Our data point to a potential metabolic link between accumulations of tyrosine and seeding of pathological aggregates in neurons as initiators for the pathological processes involved in neurodegeneration. Hence, interventions in tyrosine metabolism via regulation of NO levels may be therapeutic beneficial for the treatment of catecholamine-related neurodegenerative disorders.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Synthesis, characterization and anticancer activity of Fe(II) and Fe(III) complexes containing N-(8-quinolyl)salicylaldimine Schiff base ligands - Sutthida Wongsuwan; Jaruwan Chatwichien; Bussaba Pinchaipat; Sarawut Kumphune; David J. Harding; Phimphaka Harding; Jaursup Boonmak; Sujittra Youngme; Ratanon Chotima (JBIC Journal of Biological Inorganic Chemistry, 2021)

Quantifying the concentration dependence of sedimentation coefficients for globular macromolecules: a continuing age-old problem - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (Biophysical Reviews, 2021)
This retrospective investigation has established that the early theoretical attempts to directly incorporate the consequences of radial dilution into expressions for variation of the sedimentation coefficient as a function of the loading concentration in sedimentation velocity experiments require concentration distributions exhibiting far greater precision than that achieved by the optical systems of past and current analytical ultracentrifuges. In terms of current methods of sedimentation coefficient measurement, until such improvement is made, the simplest procedure for quantifying linear s - c dependence (or linear concentration dependence of 1/ s ) for dilute systems therefore entails consideration of the sedimentation coefficient obtained by standard c ( s ), g* ( s ) or G ( s ) analysis) as an average parameter ( $$ \overline{s} $$ s ¯ ) that pertains to the corresponding mean plateau concentration (following radial dilution) ( $$ \overline{c} $$ c ¯ ) over the range of sedimentation velocity distributions used for the determination of $$ \overline{s} $$ s ¯ . The relation of this with current descriptions of the concentration dependence of the sedimentation and translational diffusion coefficients is considered, together with a suggestion for the necessary improvement in the optical system.

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Trialling tools using hand‐weeding, weed mat and artificial shading to control nuisance macrophyte growth at multiple scales in small agricultural waterways - Kathryn E. Collins; Catherine M. Febria; Hayley S. Devlin; Kristy L. Hogsden; Helen J. Warburton; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2020)
Introduced aquatic macrophytes can dominate small agricultural waterways in summer and autumn becoming a significant management problem. Excessive growth can clog waterways, causing drainage issues and reducing agricultural productivity while in‐stream velocities are reduced and sedimentation increased. Consequently, water managers remove them by mechanical clearance, chemical spray and cutting which can be costly and have negative impacts on in‐stream habitat and ecological health. We trialled three tools to reduce macrophytes: hand‐weeding, weed mat and artificial shading, at a reach‐scale (50 m) and larger‐scale (200–400 m). Hand‐weeding reduced cover in the short‐term, however macrophytes recovered to pre‐treatment levels within one season. Weed mat along the banks was effective at reducing emergent macrophytes, particularly Erythranthe guttata (monkey musk) and Nasturtium microphyllum (watercress). Weed mat lasted for several growing seasons and continued to be effective. Shading over the waterway using polythene markedly reduced submerged macrophytes indicating that heavy shading by riparian plantings could reduce submerged macrophytes in the longer‐term. These results indicate that in the short‐term, weed mat could be used to limit sprawling emergent macrophytes. In the longer‐term, weed mat used in conjunction with riparian planting could provide shading so that macrophyte cover in these small waterways could be reduced and controlled.

Targeted Intravenous Nanoparticle Delivery: Role of Flow and Endothelial Glycocalyx Integrity - Ming J. Cheng; Ronodeep Mitra; Chinedu C. Okorafor; Alina A. Nersesyan; Ian C. Harding; Nandita N. Bal; Rajiv Kumar; Hanjoong Jo; Srinivas Sridhar; Eno E. Ebong (Annals of Biomedical Engineering, 2020)

Ecological processes mediate the effects of the invasive bloom-forming diatom Didymosphenia geminata on stream algal and invertebrate assemblages - J. P. Bray; C. Kilroy; P. Gerbeaux; F. J. Burdon; J. S. Harding (Hydrobiologia, 2020)

Multi-cellularity in cardiac tissue engineering, how close are we to native heart tissue? - Thomas J. Owen; Sian E. Harding (Journal of Muscle Research and Cell Motility, 2019)

Evaluating practical macrophyte control tools on small agricultural waterways in Canterbury, New Zealand - Kathryn E. Collins; Catherine M. Febria; Helen J. Warburton; Hayley S. Devlin; Kristy L. Hogsden; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2019)
Excessive macrophytes can cause significant problems in agricultural waterways requiring active management. Conventional control techniques can have a range of adverse effects. We investigated several control tools in two experiments: firstly, we tested eight treatments at a small‐scale (2 m × 2 m). We found intensive hand weeding, weed mat and herbicide spraying to be effective treatments, reducing macrophyte cover to

Primary care providers’ lived experiences of genetics in practice - Brittany Harding; Colleen Webber; Lucia Ruhland; Nancy Dalgarno; Christine M. Armour; Richard Birtwhistle; Glenn Brown; June C. Carroll; Michael Flavin; Susan Phillips; Jennifer J. MacKenzie (Journal of Community Genetics, 2019)

Production of membrane proteins for characterisation of their pheromone-sensing and antimicrobial resistance functions - Aalishaa A. Azam; Jean M. Kinder; G. Nasir Khan; Ade Alase; Pikyee Ma; Yang Liu; James R. Ault; Peter J. F. Henderson; Babur Z. Chowdhry; Bruce D. Alexander; Stephen E. Harding; Mary K. Phillips-Jones (European Biophysics Journal, 2018)

Interaction studies of a protein and carbohydrate system using an integrated approach: a case study of the miniagrin–heparin system - Trushar R. Patel; Tabot M. D. Besong; Markus Meier; Kevin McEleney; Stephen E. Harding; Donald J. Winzor; Jörg Stetefeld (European Biophysics Journal, 2018)

Comparative Biology of Cycad Pollen, Seed and Tissue - A Plant Conservation Perspective - J. Nadarajan; E. E. Benson; P. Xaba; K. Harding; A. Lindstrom; J. Donaldson; C. E. Seal; D. Kamoga; E. M. G. Agoo; N. Li; E. King; H. W. Pritchard (The Botanical Review, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Transgenic cowpeas (Vigna unguiculata L. Walp) expressing Bacillus thuringiensis Vip3Ba protein are protected against the Maruca pod borer (Maruca vitrata) - Bosibori Bett; Stephanie Gollasch; Andy Moore; William James; Joel Armstrong; Tom Walsh; Robert Harding; Thomas J. V. Higgins (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Acute toxicity of arsenic to larvae of four New Zealand freshwater insect taxa - Olivier Champeau; Jo Anne E. Cavanagh; Thomas J. Sheehan; Louis A. Tremblay; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2017)
Arsenic, often found in gold deposits, can enter aquatic systems. The toxicity of arsenate (As(V)), the most common valence state of arsenic in freshwater, was assessed on the larvae of four freshwater insect taxa from naturally acidic (pH 5.9) and circumneutral (pH 7.4) New Zealand streams. Insects from the acidic stream were more sensitive to arsenate‐spiked water than those from the circumneutral stream. Early instars ( Deleatidium spp. (Leptophlebiidae) were the most sensitive compared to later instars (3–6 mm) (4‐d LC 50 1.5 and 3.5 mg/L, respectively) or to the stonefly Zelandobius spp. (Gripopterygidae) (4‐d LC 50 2.5 mg/L). The cased caddisflies Pycnocentria spp. (Conoesucidae) and Helicopsyche spp. (Helicopsychidae) from circumneutral stream were the most tolerant (4‐d LC 50 45.4 and 113 mg/L, respectively). The 14‐day arsenic LC 10 and LC 50 for Deleatidium spp. late instars exposed to mining‐impacted water were 0.12 and 0.36 mg/L, respectively.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Contrasting patterns in growth and survival of Central Valley fall run Chinook salmon related to hatchery and ocean conditions - Megan C. Sabal; David D. Huff; Mark J. Henderson; Jerome Fiechter; Jeffrey A. Harding; Sean A. Hayes (Environmental Biology of Fishes, 2016)

Micro-climate influence on reference evapotranspiration estimates in wetlands - J. Kelvin; M.C. Acreman; R.J. Harding; T.M. Hess (Hydrological Sciences Journal, 2016)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Early ocean distribution of juvenile Chinook salmon in an upwelling ecosystem - Jason L. Hassrick; Mark J. Henderson; David D. Huff; William J. Sydeman; Megan C. Sabal; Jeffrey A. Harding; Arnold J. Ammann; Eric D. Crandall; Eric P. Bjorkstedt; John Carlos Garza; Sean A. Hayes (Fisheries Oceanography, 2016)
Extreme variability in abundance of California salmon populations is often ascribed to ocean conditions, yet relatively little is known about their marine life history. To investigate which ocean conditions influence their distribution and abundance, we surveyed juvenile Chinook salmon ( Oncorhynchus tshawytscha ) within the California Current (central California [37°30′N) to Newport, Oregon (44°00′N]) for a 2‐week period over three summers (2010–2012). At each station, we measured chlorophyll‐ a as an indicator of primary productivity, acoustic‐based metrics of zooplankton density as an indicator of potential prey availability and physical characteristics such as bottom depth, temperature and salinity. We also measured fork lengths and collected genetic samples from each salmon that was caught. Genetic stock identification revealed that the majority of juvenile salmon were from the Central Valley and the Klamath Basin (91–98%). We constructed generalized logistic‐linear negative binomial hurdle models and chose the best model(s) using Akaike's Information Criterion ( AIC ) to determine which covariates influenced the salmon presence and, at locations where salmon were present, determined the variables that influenced their abundance. The probability of salmon presence was highest in shallower waters with a high chlorophyll‐ a concentration and close to an individual's natal river. Catch abundance was primarily influenced by year, mean fork length and proximity to natal rivers. At the scale of sampling stations, presence and abundance were not related to acoustic indices of zooplankton density. In the weeks to months after ocean entry, California's juvenile Chinook salmon population appears to be primarily constrained to coastal waters near natal river outlets.

Anterior cingulate dopamine turnover and behavior change in Parkinson’s disease - Catherine L. Gallagher; Brian Bell; Matthew Palotti; Jen Oh; Bradley T. Christian; Ozioma Okonkwo; Jitka Sojkova; Laura Buyan-Dent; Robert J. Nickles; Sandra J. Harding; Charles K. Stone; Sterling C. Johnson; et al. (Brain Imaging and Behavior, 2015)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Stability Analysis of Coupled Heat and Mass Transfer Boundary Layers During Steam–Solvent Oil Recovery Process - M. Rabiei Faradonbeh; T. G. Harding; J. Abedi; H. Hassanzadeh (Transport in Porous Media, 2015)

Movements and site fidelity of grass shrimp (Palaemonetes pugio and P. vulgaris) in salt marsh intertidal creeks - D. M. Allen; J. M. Harding; K. B. Stroud; K. L. Yozzo (Marine Biology, 2015)

Emplacement of the Cabezo María lamproite volcano (Miocene, SE Spain) - Thomas M. Gernon; Samuel Spence; Clive N. Trueman; Rex N. Taylor; Eelco Rohling; Stuart J. Hatter; Ian C. Harding (Bulletin of Volcanology, 2015)

“Agro-meteorological indices and climate model uncertainty over the UK” - A. E. Harding; M. Rivington; M. J. Mineter; S. F. B. Tett (Climatic Change, 2015)

Variable survival across low pH gradients in freshwater fish species - P. G. Jellyman; J. S. Harding (Journal of Fish Biology, 2014)
A series of 14 day experiments was conducted on five common New Zealand fish species (redfin bully Gobiomorphus huttoni , inanga Galaxias maculatus , brown trout Salmo trutta , longfin eel Anguilla dieffenbachii and koaro Galaxias brevipinnis ) to assess the effect of pH on survival and changes in body mass. No species survived in water of pH pH 4·5, G. maculatus larvae were also tested and had high mortality at this pH . Results suggest that adults are tolerant of low‐ pH waters; however, successful remediation of anthropogenically acidified streams will require an understanding of the susceptibility to low pH on different life cycle stages.

Weak population genetic differentiation in the most numerous Arctic seabird, the little auk - Katarzyna Wojczulanis-Jakubas; Adrianna Kilikowska; Ann M. A. Harding; Dariusz Jakubas; Nina J. Karnovsky; Harald Steen; Hallvard Strøm; Jorg Welcker; Maria Gavrilo; Jan T. Lifjeld; Arild Johnsen (Polar Biology, 2014)

MultiSig: a new high-precision approach to the analysis of complex biomolecular systems - Richard B. Gillis; Gary G. Adams; Thomas Heinze; Melanie Nikolajski; Stephen E. Harding; Arthur J. Rowe (European Biophysics Journal, 2013)

Histological assessment of cerebellar granule cell layer in postmortem brain; a useful marker of tissue integrity? - Donna Sheedy; Antony Harding; Meichien Say; Julia Stevens; Jillian J. Kril (Cell and Tissue Banking, 2012)

Use of bacterial communities to assess the ecological health of a recently restored stream - G Lear; P‐Y Ancion; J Harding; GD Lewis (New Zealand Journal of Marine and Freshwater Research, 2012)
We assess the utility of bacterial community data for providing an indication of stream health in a recently ‘restored’ urban stream. A community DNA fingerprinting technique was used to characterise the bacterial community within Okeover Stream, and a lesser impacted, nearby stream. No significant differences in bacterial community structure were detected between streams. However, further investigation revealed highly elevated levels of Zn, Pb and Cu associated with microbial biofilms in Okeover Stream and an increased abundance of genes encoding for bacterial resistance to Co, Zn and Cd. Benthic invertebrates were also sampled, confirming that despite recent attempts at stream restoration, the ecological health of the Okeover Stream remains poor. While the analysis of macroinvertebrate communities appeared to provide a more informative measure of overall stream health, we show that the targeted analysis of bacterial functional genes can be used to identify possible causes of declining ecological health.

The effects of boreal forest expansion on the summer Arctic frontal zone - Stefan Liess; Peter K. Snyder; Keith J. Harding (Climate Dynamics, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands - M. C. Acreman; R. J. Harding; C. Lloyd; N. P. McNamara; J. O. Mountford; D. J. Mould; B. V. Purse; M. S. Heard; C. J. Stratford; S. J. Dury (Hydrological Sciences Journal, 2011)

Adverse foraging conditions may impact body mass and survival of a high Arctic seabird - Ann M. A. Harding; Jorg Welcker; Harald Steen; Keith C. Hamer; Alexander S. Kitaysky; Jérôme Fort; Sandra L. Talbot; Leslie A. Cornick; Nina J. Karnovsky; Geir W. Gabrielsen; David Grémillet (Oecologia, 2011)

Body size variation of a high-Arctic seabird: the dovekie (Alle alle) - Katarzyna Wojczulanis-Jakubas; Dariusz Jakubas; Jorg Welcker; Ann M. A. Harding; Nina J. Karnovsky; Dorota Kidawa; Harald Steen; Lech Stempniewicz; Cornelis J. Camphuysen (Polar Biology, 2011)

Carbon Cycling in Floodplain Ecosystems: Out-Gassing and Photosynthesis Transmit Soil δ13C Gradient Through Stream Food Webs - Duncan P. Gray; Jon S. Harding; Bo Elberling; Travis Horton; Tim J. Clough; Mike J. Winterbourn (Ecosystems, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Cryoconservation of South African plant genetic diversity - Patricia Berjak; Paul Bartels; Erica E. Benson; Keith Harding; David J. Mycock; Norman W. Pammenter; Sershen; James Wesley-Smith (In Vitro Cellular & Developmental Biology - Plant, 2011)

Multi-scale calculation and global-fit analysis of hydrodynamic properties of biological macromolecules: determination of the overall conformation of antibody IgG molecules - D. Amorós; A. Ortega; S. E. Harding; J. García de la Torre (European Biophysics Journal, 2010)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

The role of noradrenaline and 5-hydroxytryptamine in yohimbine-induced increases in alcohol-seeking in rats - Anh Dzung Lê; Douglas Funk; Stephen Harding; Walter Juzytsch; Paul J. Fletcher (Psychopharmacology, 2009)

Infectious exposure in the first year of life and risk of central nervous system tumors in children: analysis of day care, social contact, and overcrowding - N. J. Harding; J. M. Birch; S. J. Hepworth; P. A. McKinney (Cancer Causes & Control, 2009)

Can stable isotope (δ13C and δ15N) measurements of little auk (Alle alle) adults and chicks be used to track changes in high-Arctic marine foodwebs? - Ann M. A. Harding; Keith A. Hobson; Wojciech Walkusz; Kasia Dmoch; Nina J. Karnovsky; Thomas I. Van Pelt; Jan T. Lifjeld (Polar Biology, 2008)

Intra-median raphe nucleus (MRN) infusions of muscimol, a GABA-A receptor agonist, reinstate alcohol seeking in rats: role of impulsivity and reward - Anh Lê Dzung; Douglas Funk; Stephen Harding; Walter Juzytsch; Zhaoxia Li; Paul J. Fletcher (Psychopharmacology, 2008)

Identification and sequence analysis of potyviruses infecting crops in Vietnam - C. Ha; P. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

Design and application of two novel degenerate primer pairs for the detection and complete genomic characterization of potyviruses - C. Ha; S. Coombs; P. A. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Intra-median raphe nucleus (MRN) infusions of muscimol, a GABA-A receptor agonist, reinstate alcohol seeking in rats: role of impulsivity and reward - Anh Dzung Lê; Douglas Funk; Stephen Harding; Walter Juzytsch; Zhaoxia Li; Paul J. Fletcher (Psychopharmacology, 2007)

Mapping the 5′ ends of banana bunchy top virus gene transcripts - V. A. Herrera-Valencia; B. Dugdale; R. M. Harding; J. L. Dale (Archives of Virology, 2007)

Verticillium dahliae and Pratylenchus spp: populations in potato soils and plants in Australia - R. B. Harding; T. J. Wicks (Australasian Plant Pathology, 2007)

Evaluation of potato production best management practices - Bryan G. Hopkins; Donald A. Horneck; Mark J. Pavek; Brad D. Geary; Nora L. Olsen; Jason W. Ellsworth; George D. Newberry; Jeff S. Miller; Robert E. Thornton; Gale W. Harding (American Journal of Potato Research, 2007)

Direct analysis of a GPCR-agonist interaction by surface plasmon resonance - Peter J. Harding; Timothy C. Hadingham; James M. McDonnell; Anthony Watts (European Biophysics Journal, 2006)

Effects of dexfenfluramine and 5-HT3 receptor antagonists on stress-induced reinstatement of alcohol seeking in rats - Anh Dzung Lê; Douglas Funk; Stephen Harding; W. Juzytsch; Paul J. Fletcher; Yavin Shaham (Psychopharmacology, 2006)

Molecular Analysis of Fiji Disease Virus Segments 2, 4 and 7 Completes the Genome Sequence - Robert M. Harding; Parichart Burns; Robert J. Geijskes; Richard M. McQualter; James L. Dale; Grant R. Smith (Virus Genes, 2006)

Nutritional programming of adult disease - Alex J. Buckley; Anne L. Jaquiery; Jane E. Harding (Cell and Tissue Research, 2005)

COLONIZATION HISTORY OF THE BALTIC HARBOR SEALS: INTEGRATING ARCHAEOLOGICAL, BEHAVIORAL, AND GENETIC DATA - Tero Harkonen; Karin C. Harding; Simon J. Goodman; Kerstin Johannesson (Marine Mammal Science, 2005)

Method for the generation and cultivation of functional three-dimensional mammary constructs without exogenous extracellular matrix - N. E. Timmins; F. J. Harding; C. Smart; M. A. Brown; L. K. Nielsen (Cell and Tissue Research, 2005)

Longitudinal patterns in benthic communities in an urban stream under restoration - Tanya J. Blakely; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2005)
Okeover Stream, on the University of Canterbury campus in Christchurch, New Zealand, has been the subject of restoration efforts since 1998. Our study focused on quantifying the response of this urban stream to current restoration efforts. Initially, physico‐chemical conditions and biological communities at three sites along the Okeover Stream were compared with three physically similar sites on each of nearby Waimairi Stream and Avon River. General physical and chemical parameters were similar in all streams with circum‐neutral pH, specific conductivity ranging from 167 to 173 μS/cm, dissolved oxygen ranging from 9.0 to 9.2 mg/litre, low turbidity, and similar hydrological conditions. However, analysis of heavy metals in the sediment showed mean lead (Pb) concentrations in Okeover and Waimairi Streams exceeded ANZECC ISQG‐low trigger values (86.9 and 83.7 mg/kg, respectively), whereas Avon River sediment Pb levels (27.3 mg/ kg) were below trigger values. Benthic taxonomic richness did not differ significantly among the three streams. However, Okeover Stream community was dominated by the amphipod Paracalliopefluviatilis, whereas in Waimairi Stream and Avon River the gastropod snails Potamopyrgus antipodarum and Physella acuta were the dominant benthic fauna. A further assessment made at six sites along 1200 m of Okeover Stream showed no distinct longitudinal patterns in physical or chemical conditions, but there was a strong pattern in benthic macroinvertebrate communities. Taxonomic richness and caddisfly diversity increased downstream, with twice as many taxa at the most downstream site than the uppermost sampling site. In upper reaches, copper (Cu), Pb, and zinc (Zn) concentrations in sediments all exceeded ANZECC ISQG‐low trigger values. Despite ongoing restoration efforts in Okeover Stream, sedimentation, the presence of high heavy metal concentrations, intermittent flows in headwaters, and possible barriers to adult recolonisation seem to be having a continuing negative impact on benthic communities, especially in the headwaters.

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Incidence and distribution of viruses of Taro ( Colocasia esculenta ) in Pacific Island countries - P. A. Revill; G. V. H. Jackson; G. J. Hafner; I. Yang; M. K. Maino; M. L. Dowling; L. C. Devitt; J. L. Dale; R. M. Harding (Australasian Plant Pathology, 2005)

Investigations into the seed and mealybug transmission of Taro bacilliform virus - A. R. Macanawai; A. A. Ebenebe; D. Hunter; L. C. Devitt; G. J. Hafner; R. M. Harding (Australasian Plant Pathology, 2005)

Sugarcane bacilliform virus encapsidates genome concatamers and does not appear to integrate into the Saccharum officinarum genome - R. J. Geijskes; K. S. Braithwaite; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Molecular analysis of Fiji disease virus genome segments 5, 6, 8 and 10 - R. B. McQualter; P. Burns; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Measurement of the skin microcirculation through intact bandages using laser Doppler flowmetry - J. M. Melhuish; L. Krishnamoorthy; T. Bethaves; M. Clark; R. J. Williams; K. G. Harding (Medical & Biological Engineering & Computing, 2004)

Analysis of variability in partial sequences of genomes of Tobacco yellow dwarf virus isolates - B. van Rijswijk; B. C. Rodoni; P. A. Revill; J. E. Thomas; J. R. Moran; R. M. Harding (Australasian Plant Pathology, 2004)

Petrographic analysis using cathodoluminescence microscopy with simultaneous energy-dispersive X-ray spectroscopy - W. Vortisch; D. Harding; J. Morgan (Mineralogy and Petrology, 2003)

Sequence diversity of South Pacific isolates of Taro bacilliform virus and the development of a PCR-based diagnostic test - I. C. Yang; G. J. Hafner; P. A. Revill; J. L. Dale; R. M. Harding (Archives of Virology, 2003)

Contractile effects of adenovirally-mediated increases in SERCA2a activity: A comparison between adult rat and rabbit ventricular myocytes - Babar Chaudhri; Federica del Monte; Roger J. Hajjar; Sian E. Harding (Molecular and Cellular Biochemistry, 2003)

A promoter derived from taro bacilliform badnavirus drives strong expression in transgenic banana and tobacco plants - I. C. Yang; J. P. Iommarini; D. K. Becker; G. J. Hafner; J. L. Dale; R. M. Harding (Plant Cell Reports, 2003)

Genomic characterisation of taro bacilliform virus - I. C. Yang; G. J. Hafner; J. L. Dale; R. M. Harding (Archives of Virology, 2003)

Sequence analysis of an Australian isolate of sugarcane bacilliform badnavirus - R. J. Geijskes; K. S. Braithwaite; J. L. Dale; R. M. Harding; G. R. Smith (Archives of Virology, 2002)

Lidar remote sensing of above‐ground biomass in three biomes - Michael A. Lefsky; Warren B. Cohen; David J. Harding; Geoffrey G. Parker; Steven A. Acker; S. Thomas Gower (Global Ecology and Biogeography, 2002)
Estimation of the amount of carbon stored in forests is a key challenge for understanding the global carbon cycle, one which remote sensing is expected to help address. However, estimation of carbon storage in moderate to high biomass forests is difficult for conventional optical and radar sensors. Lidar ( li ght d etection and r anging) instruments measure the vertical structure of forests and thus hold great promise for remotely sensing the quantity and spatial organization of forest biomass. In this study, we compare the relationships between lidar‐measured canopy structure and coincident field measurements of above‐ground biomass at sites in the temperate deciduous, temperate coniferous, and boreal coniferous biomes. A single regression for all three sites is compared with equations derived for each site individually. The single equation explains 84% of variance in above‐ground biomass ( P

Promoters derived from banana bunchy top virus-associated components S1 and S2 drive transgene expression in both tobacco and banana - S. Hermann; D. Becker; R. Harding; J. Dale (Plant Cell Reports, 2001)

Surface fluxes of heat and water vapour from sites in the European Arctic - C. R. Lloyd; R. J. Harding; T. Friborg; M. Aurela (Theoretical and Applied Climatology, 2001)

Progress in understanding of land surface/atmosphere exchanges at high latitudes - R. J. Harding; S.-E. Gryning; S. Halldin; C. R. Lloyd (Theoretical and Applied Climatology, 2001)

The Scientific Foundations of Habitat Conservation Plans: a Quantitative Assessment - Elaine K. Harding; Elizabeth E. Crone; Bret D. Elderd; Jonathan M. Hoekstra; Alexa J. McKerrow; John D. Perrine; Jim Regetz; Leslie J. Rissler; Amanda G. Stanley; Eric L. Walters; Nceas Habitat Conservation Plan Working Group (Conservation Biology, 2001)
The number of habitat conservation plans ( HCP) has risen dramatically since the first plan was written over 18 years ago. Until recently, no studies have quantitatively investigated the scientific foundations underlying these documents. As part of a larger study of HCPs, we examined 43 plans primarily to assess the availability and use of scientific data and secondarily to determine the extent of involvement by, and influence of, independent scientists within the process. Specifically, our analysis focused on five key steps taken when an HCP is developed: assessing status of a species, determining take, predicting the project effects, mitigating for those effects, and monitoring of take and mitigation. In general, we found that the preparers of HCPs utilized existing scientific information fairly well, with 60% of plans not missing any available information described by our study as “starkly necessary.” The most common types of underutilized available data included those describing the influence of stochastic processes and habitat quality or quantity on species persistence. For many species, however, data on biology or status simply did not exist, as demonstrated by the fact that we could locate quantitative population estimates for only 10% of the species. Furthermore, for 42% of the species examined we had insufficient data and analysis to determine clearly how predicted take might affect the population. In many cases, mitigation measures proposed to offset take frequently addressed the most important local threats to the species with moderately reliable strategies. Species with monitoring programs rated as sufficient had plans that proposed to collect a greater amount of “quantitative” data than did those programs rated insufficient. Finally, when species “experts” were consulted, plan quality was generally higher. Overall, available scientific information in a majority of categories was fairly well utilized, but for many species additional studies and more in‐depth analyses were required to provide adequate support for issuance of an incidental take permit.

Intron-mediated enhancement of the banana bunchy top virus DNA-6 promoter in banana (Musa spp.) embryogenic cells and plants - B. Dugdale; D.K. Becker; R.M. Harding; J. L. Dale (Plant Cell Reports, 2001)

Additional Rep-encoding DNAs associated with banana bunchy top virus - C. L. Horser; M. Karan; R. M. Harding; J. L. Dale (Archives of Virology, 2001)

The relationship of BRMS1 and RhoGDI2 gene expression to metastatic potential in lineage related human bladder cancer cell lines - M. Jabed Seraj; Michael A. Harding; John J. Gildea; Danny R. Welch; Dan Theodorescu (Clinical & Experimental Metastasis, 2000)

Trp203 mutation in GroEL promotes a self-association reaction: a hydrodynamic study - Chris Walters; Anthony Clarke; Matthew J. Cliff; Peter A. Lund; Stephen E. Harding (European Biophysics Journal, 2000)

Promoters derived from banana bunchy top virus DNA-1 to −5 direct vascular-associated expression in transgenic banana ( Musa spp.) - B. Dugdale; D. K. Becker; P. R. Beetham; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

The role of corticotrophin-releasing factor in stress-induced relapse to alcohol-seeking behavior in rats - A. D. Lê; S. Harding; W. Juzytsch; J. Watchus; U. Shalev; Y. Shaham (Psychopharmacology, 2000)

Koala Conservation Policy Process: Appraisal and Recommendations - Tim W. Clark; Nicole Mazur; Steven J. Cork; Steve Dovers; Ronnie Harding (Conservation Biology, 2000)
Australia's koalas are a global treasure, yet there is growing concern that present policy may not adequately conserve viable, wild populations in abundant habitats. Problems in the content and particularly the process of policy making for koala conservation include integrating reliable knowledge and diverse perspectives. We reviewed the overall decision process involved in developing Koala conservation policy, including the functions of intelligence, promotion, prescription, invocation, application, appraisal, and termination. To date, intelligence ( planning ) has lacked social science data, and promotion (open debate) has been confrontational. Koala policy has been unclear about prescription (setting rules) and lacks specificity about needed standards, penalties for violating standards, and making resources available. Invocation and application (implementation) have been differentially successful. Appraisal has been adversarial and incomplete, and termination of weak practices has been difficult. We suggest implementation of procedural standards such as timeliness, comprehensiveness, and rationality for a better koala decision process. The 1998 National Koala Conservation Strategy and various state policies can be upgraded to meet these standards. Opportunities exist to improve koala management policy in all seven functions. We recommend a three‐part strategy: (1) identify, describe, and appraise successful conservation efforts to find the best practices, (2) disseminate success stories, and (3) open up new opportunities for improvement in all aspects of koala conservation.

Sequence variability in the coat protein gene of two groups of banana bunchy top isolates - R. Wanitchakorn; R. M. Harding; J. L. Dale (Archives of Virology, 2000)

Genetic transformation of Cavendish banana ( Musa spp. AAA group) cv 'Grand Nain' via microprojectile bombardment - D. K. Becker; B. Dugdale; M. K. Smith; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

5′-Anchored simple-sequence repeat primers are useful for analysing potato somatic hybrids - D. Matthews; J. McNicoll; K. Harding; S. Millam (Plant Cell Reports, 1999)

Minisatellite mutational processes reduce F st estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Minisatellite mutational processes reduce Fst estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Taxonomic implications for Fijiviruses based on the terminal sequences of Fiji disease fijivirus - J. A. McMahon; J. L. Dale; R. M. Harding (Archives of Virology, 1999)

National Recreation Trails: A Forgotten Designation - Deborah J. Chavez; James A. Harding; Joanne F. Tynon (Journal of Forestry, 1999)
What value does federal designation add to open space resources that are not all federally owned and managed? Over the years the federal government, under the auspices of the National Park Service and USDA Forest Service, has designated trails across the United States as National Recreation Trails. A survey of federal, nonfederal public, and private National Recreation Trail managers indicated that few knew they maintained a federally designated trail. As a result, the managers could not use the designation to help them manage the trails. The time is right to revitalize this system.

Characterization and expression of the coat protein-coding region of banana bract mosaic potyvirus, development of diagnostic assays and detection of the virus in banana plants from five countries in southeast Asia - B. C. Rodoni; J. L. Dale; R. M. Harding (Archives of Virology, 1999)

Lateral Vibrations by Social Wasps Signal Larvae to Withhold Salivary Secretions (Polistes fuscatus, Hymenoptera: Vespidae) - Danielle L. D. Cummings; George J. Gamboa; Bobbi J. Harding (Journal of Insect Behavior, 1999)

Calculation of NMR relaxation, covolume, and scattering-related properties of bead models using the SOLPRO computer program - J. García de la Torre; Stephen E. Harding; Beatriz Carrasco (European Biophysics Journal, 1999)

Measurement of forces associated with compression therapy - D. Wertheim; J. Melhuish; R. Williams; K. Harding (Medical & Biological Engineering & Computing, 1999)

Banana bunchy top virus DNA-2 to 6 are monocistronic - P. R. Beetham; R. M. Harding; J. L. Dale (Archives of Virology, 1999)

Heavy and Trace Metals in Wild Mink ( Mustela vison ) and River Otter ( Lontra canadensis ) Captured on Rivers Receiving Metals Discharges - L. E. Harding; M. L. Harris; J. E. Elliott (Bulletin of Environmental Contamination and Toxicology, 1998)

Ultracentrifugation studies on the transmembrane domain of the human erythrocyte anion transporter Band 3 in the detergent C 12 E 8 - H. Cölfen; J. M. Boulter; Stephen E. Harding; Anthony Watts (European Biophysics Journal, 1998)

Quantitative analysis of correlations among flower traits in Gerbera hybrida, Compositae. III. Genetic variability and structure of principal component traits - H. Huang; J. Harding (Theoretical and Applied Genetics, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Sequence diversity in the coat protein coding region of twelve sugarcane mosaic potyvirus isolates from Australia, USA and South Africa - J. A. Handley; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Reproductive biology of the endemic goby, Lentipes concolor, from Makamaka'ole Stream, Maui and Waikolu Stream, Moloka'i - Carl M. Way; Albert J. Burky; Juliana M. Harding; Skippy Hau; William K.L.C. Puleloa (Environmental Biology of Fishes, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Banana bunchy top virus DNA-3encodes the viral coat protein - R. Wanitchakorn; R. M. Harding; J. L. Dale (Archives of Virology, 1997)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)

Low temperature solution behaviour of Methylophilus methylotrophus electron transferring flavoprotein: a study by analytical ultracentrifugation - H. Cölfen; S. E. Harding; Emma K. Wilson; Nigel S. Scrutton; Donald J. Winzor (European Biophysics Journal, 1997)

SOLPRO: theory and computer program for the prediction of SOLution PROperties of rigid macromolecules and bioparticles - J. García de la Torre; Beatriz Carrasco; Stephen E. Harding (European Biophysics Journal, 1997)

A slot-blot hybridisation method for screening somatic hybrids - D. Matthews; K. Harding; M. J. Wilkinson; S. Millam (Plant Molecular Biology Reporter, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A gene tree for β-globin sequences from melanesia - R. M. Harding; S. M. Fullerton; R. C. Griffiths; J. B. Clegg (Journal of Molecular Evolution, 1997)

Sequence diversity in the NIb coding region of eight sugarcane mosaic potyvirus isolates infecting sugarcane in Australia - J. A. Handley; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 1996)

Handwipe sampling and analysis procedure for the measurement of dermal contact with pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos; R. G. Lewis (Archives of Environmental Contamination and Toxicology, 1996)

Handwipe Sampling and Analysis Procedure for the Measurement of Dermal Contact with Pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos (Archives of Environmental Contamination and Toxicology, 1996)

Expression, purification, and use as an antigen of recombinant sugarcane mosaic virus coat protein - G. R. Smith; R. Ford; J. D. Bryant; R. L. Gambley; T. K. McGhie; R. M. Harding; J. L. Dale (Archives of Virology, 1995)

Detection and characterization of pangola stunt Fijivirus from Australia using cloned cDNA probes - M. Karan; J. L. Dale; M. F. Bateson; R. M. Harding; D. S. Teakle (Archives of Virology, 1994)

Evidence that banana bunchy top virus has a multiple component genome - T. M. Burns; R. M. Harding; J. L. Dale (Archives of Virology, 1994)

A monoclonal antibody which recognizes cell surface antigen and inhibits porcine parvovirus replication - M. J. Harding; T. W. Molitor (Archives of Virology, 1992)

Influence of seed placement on Russet Burbank potato yield and grade - J. L. Halderson; J. C. Ojala; G. W. Harding; E. V. Musselman (American Journal of Potato Research, 1992)

Porcine parvovirus: replication in and inhibition of selected cellular functions of swine alveolar macrophages and peripheral blood lymphocytes - M. J. Harding; T. W. Molitor (Archives of Virology, 1988)